Early Transcriptional Events During Osteogenic Differentiation of Human Bone Marrow Stromal Cells Induced by Lim Mineralization Protein 3 - Bernardini, Camilla (Gene Expr, 2018)
Lim mineralization protein-3 (LMP3) induces osteoblast differentiation by regulating the expression and activity of certain molecules involved in the osteogenic cascade, including those belonging to the bone morphogenetic protein (BMP) family. The complete network of molecular events involved in LMP3-mediated osteogenesis is still unknown. The aim of this study was to analyze the genome-wide gene expression profiles in human mesenchymal stem cells (hMSC) induced by exogenous LMP3 to mediate osteogenesis. For this purpose hMSC were transduced with a defective adenoviral vector expressing the human LMP3 gene and microarray analysis was performed 1 day post-adenoviral transduction. Cells transduced with the vector backbone and untransduced cells were used as independent controls in the experiments. Microarray data were independently validated by means of real-time PCR on selected transcripts. The statistical analysis of microarray data produced a list of 263 significantly (p < 0.01) differentially expressed transcripts. The biological interpretation of the results indicated, among the most noteworthy effects, the modulation of genes involved in the TGF-β1 pathway: 88 genes coding for key regulators of the cell cycle regulatory machinery and 28 genes implicated in the regulation of cell proliferation along with the development of connective, muscular, and skeletal tissues. These results suggested that LMP3 could affect the fine balance between cell proliferation/differentiation of mesenchymal cells mostly by modulating the TGF-β1 signaling pathway.